Photosynthesis and Inorganic Carbon Accumulation in the Acidophilic Alga Cyanidioschyzon merolae - Zenvirth, Drora (1985)
The intracellular pH and membrane potential were determined in the acidophilic algae Cyanidoschyzon merolae as a function of extracellular pH. The alga appear to be capable of maintaining the intracellular pH at the range of 6.35 to 7.1 over the extracellular pH range of 1.5 to 7.5. The membrane potential increase from −12 millivolts (negative inside) to −71 millivolts and thus Δμ̃H(+) decreased from −300 to −47 millivolts over the same range of extracellular pH. It is suggested that the Δμ̃H(+) may set the upper and lower limits of pH for growth. Photosynthetic performance was also determined as a function of pH. The cells appeared to utilize CO(2) from the medium as the apparent K(m(co(2))) was 2 to 3 micromolar CO(2) over the pH range of 1.5 to 7.5 C. merolae appear to possess a `CO(2) concentrating' mechanism.